Proceedings of the 14th International Conference on Interaction Design and Children 2015
DOI: 10.1145/2771839.2771910
|View full text |Cite
|
Sign up to set email alerts
|

"Siri, is this you?"

Abstract: The increasing pervasiveness of voice input systems in consumer devices (e.g., Apple's iOS Siri) creates the potential for young children to use features and access content that previously required the ability to read and write. However, whether and how young children use voice input systems and associated voice agents on mainstream devices has not been studied in detail. This paper reports preliminary findings from an online survey with parents about children's use of voice input systems and a content analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(31 citation statements)
references
References 9 publications
2
28
0
1
Order By: Relevance
“…Preliminary research into DVAs has shown not only how they are integrated into daily family life (Porcheron, Fischer, Reeves, & Sharples, 2018;Beirl, Yuill, & Rogers, 2019) and how families use various strategies to overcome communication barriers with DVAs (Beneteau et al, 2019), but also how children probe and explore different dimensions of DVAs' perceived intelligence (e.g., how accurately and consistently DVAs answer knowledgebased questions), their preprogrammed personality traits, and their conversational capabilities (Lovato & Piper, 2015;Druga, Williams, Breazeal, & Resnick, 2017;Druga, 2018;Sciuto, Saini, Forlizzi, & Hong, 2018;Lovato, Piper, & Wartella, 2019).…”
Section: Literature Review Of Child-machine Interactionmentioning
confidence: 99%
“…Preliminary research into DVAs has shown not only how they are integrated into daily family life (Porcheron, Fischer, Reeves, & Sharples, 2018;Beirl, Yuill, & Rogers, 2019) and how families use various strategies to overcome communication barriers with DVAs (Beneteau et al, 2019), but also how children probe and explore different dimensions of DVAs' perceived intelligence (e.g., how accurately and consistently DVAs answer knowledgebased questions), their preprogrammed personality traits, and their conversational capabilities (Lovato & Piper, 2015;Druga, Williams, Breazeal, & Resnick, 2017;Druga, 2018;Sciuto, Saini, Forlizzi, & Hong, 2018;Lovato, Piper, & Wartella, 2019).…”
Section: Literature Review Of Child-machine Interactionmentioning
confidence: 99%
“…In addition, our study suggests that the roots of usability and accessibility challenges for other populations--like older adults, children, people with Alzheimer's, and people with intellectual disabilities--may be traced back to VAPA design guidelines. Prior work finds that speech recognition often breaks down for children and older adults [3,21] as well as people who are deaf or hard-of-hearing [16], because there is wide variation in pitch, pronunciation, patterns of stress, and intersyllabic pauses, leading to higher recognition error rates [16,21,35]. Prior work also finds that the timeout period for speech input is often inadequate for people with Alzheimer's [34] and intellectual disabilities [3].…”
Section: Putting Disability Back Into the Ideal Humanmentioning
confidence: 99%
“…There are two reasons for this decision. First, these interactions represent an im- [4] and the plurality (45%) of children's interactions with Apple's Siri [36] fell into the information seeking and web search categories. Second, there is substantial potential for leveraging speech interfaces to address a number of challenges that children face with current text-based search practices.…”
Section: Children's Informational Query Practicesmentioning
confidence: 99%
“…It may be even more difficult for children, but little is known about children's practices with speech interface query reformulation. Previous exploratory work that has examined children's interaction with Apple's Siri through a content review of YouTube videos found that children had substantial trouble dealing with speech interface errors, relying mostly on phonetic emphasis in reformulation [36]. Additionally, in a study with a similar WoZ design to ours, Oviatt et al found that children change the prosodic (e.g., speed, pitch) qualities of their speech to match an animated agent's [48], but did not investigate semantic reformulations or adaptations.…”
Section: Children's Informational Query Practicesmentioning
confidence: 99%
See 1 more Smart Citation